2023
DOI: 10.1093/cei/uxad033
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune/inflammatory syndrome induced by adjuvants (ASIA): past, present, and future implications

Abstract: Summary Adjuvants, as the name indicates, are adjoined material aimed to assist in functioning as when added to vaccines they are meant to boost the effect and strongly stimulate the immune system. The response of the immune system can be unpredictable, and the autoimmune/inflammatory syndrome induced by adjuvants (ASIA) was developed to address possible adverse reactions of an autoimmune and inflammatory type that may be caused by adjuvants. While ASIA, as a syndrome, was coined and defined in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 172 publications
0
2
0
Order By: Relevance
“…This encompasses a set of immune reactions caused by certain compounds found in vaccines, such as silicone, aluminum, or infectious components [ 191 , 192 ]. Watad et al studied 500 patients aged 43 ± 17 years with ASIA syndrome and found that 89% were women, thus suggesting a higher risk of developing this condition compared to men [ 193 , 194 ].…”
Section: Sex Differences In Vaccine Outcomementioning
confidence: 99%
“…This encompasses a set of immune reactions caused by certain compounds found in vaccines, such as silicone, aluminum, or infectious components [ 191 , 192 ]. Watad et al studied 500 patients aged 43 ± 17 years with ASIA syndrome and found that 89% were women, thus suggesting a higher risk of developing this condition compared to men [ 193 , 194 ].…”
Section: Sex Differences In Vaccine Outcomementioning
confidence: 99%
“…Moreover, using adjuvants in the production of vaccines has been thought to be a major risk factor for triggering autoimmune diseases. 64 In addition, cross-reactivity between the vaccine and host cells is another possible mechanism as similarities were found between SARS-CoV-2 spike protein and human proteins. 65 As some COVID-19 vaccines are mRNA-based vaccines, they can increase the production of type 1 interferons which is implicated in the pathophysiology of SLE.…”
Section: Mechanisms In Which Vaccines Can Trigger Slementioning
confidence: 99%